SiBARIS for Transparent and Efficient Regional Asset Management: SiBARIS untuk Pengelolaan Aset Regional yang Transparan dan Efisien - Aminy, Ritzana Aisyah; Eviyanti, Ade; Ariyanti, Novia; Rosid, Mochamad Alfan (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Regional government-owned assets are essential resources that support public service delivery and administrative efficiency. Specific Background: In Sidoarjo Regency, asset management remains constrained by manual processes and limited integration of visual and locational data. Knowledge Gap: Previous systems improved data recording but lacked real-time tracking and digital documentation of asset handovers. Aims: This study developed SiBARIS (Sistem Informasi Barang Milik Daerah dengan Informasi Lokasi), a web-based system designed to optimize inventory and handover management of regional assets at BPKAD Sidoarjo. Results: The system, built using Laravel and MySQL with the Waterfall method, integrates photo uploads, GPS-based tracking, and automated digital handover documentation, demonstrating significant improvements in data accuracy, transparency, and administrative efficiency. Novelty: SiBARIS introduces a comprehensive digital platform combining asset documentation, location tracking, and automatic reporting in one unified system. Implications: This innovation contributes to more transparent, accountable, and efficient local governance, serving as a model for digital asset management in regional government institutions. Highlights: Web-based system integrating visual and GPS data for asset tracking. Improves transparency and accountability in local asset management. Serves as a replicable model for regional digital governance. Keywords: SiBARIS, Regional Assets, Inventory System, Public Administration, Transparency